Education quality comparing between official measurement scale and inter-counterparts' perception: a new horizon for learning assessment - Alam, Gazi Mahabubul; Forhad, Md. Abdur Rahman (Inderscience Enterprises, 2022)
Referring to the official measurement scale, global evidences confirm that 'education quality' has continuously been improving. On the other hand, studies examining the role of education discover that education continuously fails to play the desired role. Therefore, claims are made that 'education quality' is denting. Keeping this view in mind, this research is conducted to assess the education quality, making a comparison between the official measurement scale and 'inter-counterparts' perception'. Both primary and secondary data are used. According to the official measurement scale, 'education quality' has been improved substantially for every provision-primary to tertiary. Apparently, the entire system functions well where performances and 'education quality' of all provisions are synchronised. On the other hand, 'inter-counterparts' perception' indicates that 'education quality' of all provisions deteriorates gradually and they live in an isolation. This research suggested a new horizon for assessment which would ensure substantial learning outcomes; helping the developing world.